Acquisition of Complement Inhibitor Serine Protease Factor I and Its Cofactors C4b-Binding Protein and Factor H by Prevotella intermedia - Malm, Sven (Public Library of Science, 2012)

(untitled)
Infection with the Gram-negative pathogen Prevotella intermedia gives rise to periodontitis and a growing number of studies implies an association of P. intermedia with rheumatoid arthritis. The serine protease Factor I (FI) is the central inhibitor of complement degrading complement components C3b and C4b in the presence of cofactors such as C4b-binding protein (C4BP) and Factor H (FH). Yet, the significance of complement inhibitor acquisition in P. intermedia infection and FI binding by Gram-negative pathogens has not been addressed. Here we show that P. intermedia isolates bound purified FI as well as FI directly from heat-inactivated human serum. FI bound to bacteria retained its serine protease activity as shown in degradation experiments with (125)I-labeled C4b. Since FI requires cofactors for its activity we also investigated the binding of purified cofactors C4BP and FH and found acquisition of both proteins, which retained their activity in FI mediated degradation of C3b and C4b. We propose that FI binding by P. intermedia represents a new mechanism contributing to complement evasion by a Gram-negative bacterial pathogen associated with chronic diseases.